Efektivitas Festival Anak dalam Meningkatkan Kreatifitas Siswa - Ali Daud Hasibuan; Fadilla Zalzabila Lubis; Aisyah Amini; Susmayati Susmayati; Raydatul Safitri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Children's Day Festival, celebrated every July 23, is a strategic moment in supporting children's holistic development. Through various activities such as fashion shows, poetry readings, coloring, and adhan, this festival not only serves as entertainment but also as a non-formal educational tool that aims to instill moral, social, cultural, and religious values in children. These activities are designed to enhance creativity, self-confidence, respect, empathy, courage, and strengthen local cultural identity, thereby contributing to the overall character and personality development of children. This study confirms that this festival plays an important role in supporting sustainable child growth and development oriented towards self-potential development. It is recommended that this activity continue to be developed and adapted to the times, involving various related parties, and evaluated periodically to ensure its effectiveness in achieving the goals of character education and child development.